2007
DOI: 10.1614/wt-07-068.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizings-Metolachlor and Dimethenamid-P in Sugarbeet Microrate Treatments

Abstract: Field trials were conducted in East Lansing, MI in 2004 and 2005 and in St. Charles, MI in 2004, 2005, and 2006 to compare weed control and sugarbeet tolerance from microrate herbicide treatments that includeds-metolachlor and dimethenamid-P. Treatments included the base microrate treatment alone and with full- and split-application rates ofs-metolachlor at 1.4 kg/ha or dimethenamid-P at 0.84 kg/ha at the various microrate application timings. All treatments injured sugarbeet. In 2004 and 2006, full rates of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Smith and Schweizer (1983) reported that sugarbeet can recover from stature reduction caused by herbicides applied PRE and POST in spring and early summer and yield similarly to weed-free treatments. Likewise, Bollman and Sprague (2007) reported that sugarbeet overcame injury caused by PRE herbicides applied under different tillage regimes and closed canopy and produced recoverable sucrose the same as untreated control comparisons. Sugarbeet also compensate for stand loss.…”
mentioning
confidence: 92%
“…Smith and Schweizer (1983) reported that sugarbeet can recover from stature reduction caused by herbicides applied PRE and POST in spring and early summer and yield similarly to weed-free treatments. Likewise, Bollman and Sprague (2007) reported that sugarbeet overcame injury caused by PRE herbicides applied under different tillage regimes and closed canopy and produced recoverable sucrose the same as untreated control comparisons. Sugarbeet also compensate for stand loss.…”
mentioning
confidence: 92%
“…Similarly, S-metolachlor is applied PRE for weed control in various vegetable crops. Bollman and Sprague (2007) reported 94% control of pigweed (Amaranthus spp.) species with S-metolachlor applied at 1.4 kg ai ha À1 .…”
mentioning
confidence: 99%
“…Sugarbeet density, stature reduction, root yield, sucrose content, and recoverable sucrose in response to S-metolachlor application, averaged across environments with less than and greater than 3.5% organic matter content and greater than 40-mm cumulative rainfall through 14 d after application in 2015, 2016, and 2017. and early summer, and yield was similar to that of weed-free, untreated checks. Likewise, Bollman and Sprague (2007) reported sugarbeet overcoming injury caused by PRE herbicides applied under different tillage regimes and closed canopy and producing recoverable sucrose the same as untreated control comparisons. Sugarbeet also compensates for stand loss.…”
Section: Rainfall Om Soil Series and S-metolachlor Ratementioning
confidence: 91%